16.4: Fully R2R‐Processed Flexible OLEDs for Lighting. Issue 1 (June 2015) - Minakata, Takashi; Tanamura, Mitsuru; Mitamura, Yasuhiro; Imashiro, Masayuki; Horiguchi, Akira; Sugimoto, Akira; Yamashita, Masahiko; Ujiiye, Kento; Sunahiro, Satoshi; Yada, Yukito; Ibaraki, Nobuki; Tomiyasu, Hiroshi
Abstract : Flexible organic light‐emitting diodes (OLEDs) on continuous plastic film have been successfully fabricated using full roll‐toroll (R2R) processes, including depositions of gas‐barrier layers, electrodes, layered‐organic semiconductors, and lamination encapsulation. The OLEDs exhibit excellent stability and high performance comparable to OLEDs on glass, with the incorporation of R2R deposited high‐gas‐barrier layer with a WVTR below 10‐ 5 g/m 2 day. Also a strong correlation between the gas‐barrier performance and the stability of the OLEDs stored in high humidity environment has been confirmed.